O índice de desenvolvimento humano do município de Amajari-Roraima: uma análise do período 1991-2010 - Campelo, Lucicleide Lopes (2017)
This work analyzed the human developmenk index of the municipality of amajari-roraima, between 1991 a 2010, and had as objective check the motives of low index of IDH-M, because the municipality failed to achieve a good performance over the historic serie disclosed by the United nations program to the development (PNUD), whose last publication was in 2013.Due to the fact that the municipality has among the worst in the ranking do IDH-M in Brazil, it was hypothesized that public policies have not been efficient for the growth of the index during the period. Therefore was realized a study about the concept of human development to extend the questions related to what can promote the human development.Was also made a study about one the calculation methodology of IDH to check the variables that are used in the model.besides that, was realized a study about the concept of public policy and a study socioeconomic of the municipality since your creation for check the performance of the economy and investigate wich public policies were applied in the municipality during the period. For being a municipality with a strong indigenous population concetration was realized an analysis about the concept of pre-capitalist communities to understand wich are the activities and the culture of non-monetized communities.The data used to the analyses were extracted from IBGE, secretary of planning the state of Roraima (SEPLAN) and atlas of human development in Brazil that made it easier the analyses of the condutions of human development in the municipality, in order to demonstrate the level of evolution of the index and compare the level municipal with the state and national.With that it was possible to check that even with a positive variation of the dimensions over the period, the longevity was the only on that stood out having a result considered low wich contributes for the low and result of the IDH-M.One this, the hypothesis was deconstructed, because only public policies would not solve the problems of the municipality is in a situation.Where part of your population still lives in a pre-capitalist system,where the income and the common education in the capitalisty system not part of the daily of this parcel of countius,therewith,it was clear that the cultural factor weighed in the result of the index and was checked that the IDH isn't still the methodo most aporopriate to measure the level well-being this municipality, because for the most part of these individuals these variables used in the calculation of the index aren't still the priorities in the daily life this population.